Characteristics of adrenal incidentalomas in a New Zealand centre. Issue 2 (7th February 2018) - Goh, Ziwei; Phillips, Ian; Hunt, Penny J.; Soule, Steven; Cawood, Tom J.
Abstract: Background: Management of adrenal incidentalomas (AI) is becoming more conservative, based on international data showing a low incidence of functional or malignant lesions. The clinical characteristics of AI in New Zealand are unknown. Therefore, whether the AI guidelines apply to the New Zealand population is also unknown. Aims: To investigate the clinical characteristics of patients with AI presenting to a tertiary‐care centre in New Zealand. Method: This study prospectively evaluated consecutive patients aged 18 or older with AI, 1 cm or larger, diagnosed in Canterbury, New Zealand. A standardised nurse‐led dedicated AI clinic was used, including clinical assessment, hormonal evaluation and imaging. Results: From January 2010 to April 2016, 306 patients were referred to the AI clinic, 228 met the inclusion criteria. Most of those excluded were not true AI, due to imaging performed for known or suspected non‐adrenal malignancy. The most common reason for imaging was abdominal pain (46%). Most cases were benign (96.5%) and 88.6% of all cases were non‐functional. Of the functioning tumours (26 patients), 18 had subclinical Cushing syndrome, four had late‐onset congenital adrenal hyperplasia, two had phaeochromocytoma and one had primary hyperaldosteronism. Three patients had primary adrenal cancer, one of whom was secreting excess cortisol. One adrenal metastasis was diagnosed. Conclusion: This study found a similar prevalence of functional and malignant AI as international centres, although mild cortisol excess and primary aldosteronism may be under‐represented. Therefore, the conservative approach to management of AI recommended in current guidelines is likely to be applicable to New Zealand population.